Justice Work: Sisters (Having to) Do It for Themselves: Women’s Experiences of the Criminal Justice System When Reporting Domestic Abuse and Stalking - Lombard, Nancy (The British journal of criminology, 2025)
This article outlines findings from our research which sought to explore the lived experiences of victim/survivors of stalking and/or coercive control as they navigated their way through the Scottish Criminal Justice System (SCJS), commissioned by the Scottish Government. Building on the work of Acker (1990), Hochschild (1983), Fishman (1978), Kelly (2016) and Vera-Gray (2018; 2020) our findings show that women’s involvement as victim-survivors with the criminal justice system insists they perform elements of both hidden (behind the scenes) and visible (but unacknowledged) work. These types of work replicate already identified elements of emotional, safety and violence work. In addition, however, we uncovered a new form of work that women must undertake when seeking justice which we have conceptualized as ‘Justice Work’.